2014
DOI: 10.1080/1369118x.2014.946434
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the potential and problems of digital methods through action research: methodological reflections

Abstract: This paper reports on an action research project with public sector organisations in the UK which experimented with a range of digital methods (social media data mining, social network and issue network mapping, data visualisation), in order to explore their potential usefulness for the public engagement activities of these organisations. We argue that there is a need for small-scale, qualitative studies of cultures of large-scale, quantitative data like ours, to open up spaces in which to reflect critically o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 23 publications
0
37
0
2
Order By: Relevance
“…In particular, scholars' scepticism concerning skills barriers goes hand in hand with their claims about expertise-related barriers to the use of digital, social or big data by individuals and organisations (Bassett, 2015;Kennedy et al, 2014. For instance, in their study of public sector organisations' use of digital data analysis tools, Kennedy et al (2014 found a skills and expertise divide in data generation and collection, use of datacollection tools and data analysis. However, do skills and expertise divides of this nature comprise the core of the literacy challenges that researchers encounter in digital research?…”
Section: Digital Methods Data and Expertisementioning
confidence: 99%
See 3 more Smart Citations
“…In particular, scholars' scepticism concerning skills barriers goes hand in hand with their claims about expertise-related barriers to the use of digital, social or big data by individuals and organisations (Bassett, 2015;Kennedy et al, 2014. For instance, in their study of public sector organisations' use of digital data analysis tools, Kennedy et al (2014 found a skills and expertise divide in data generation and collection, use of datacollection tools and data analysis. However, do skills and expertise divides of this nature comprise the core of the literacy challenges that researchers encounter in digital research?…”
Section: Digital Methods Data and Expertisementioning
confidence: 99%
“…Such barriers include the narrow scope of datasets; limited access; poor data quality, veracity and fidelity; ill-defined lineage; poor interoperability; suspect analytics and ecological fallacies; and a weakly developed skills base and organisational receptiveness (Kitchin, 2014b). In particular, scholars' scepticism concerning skills barriers goes hand in hand with their claims about expertise-related barriers to the use of digital, social or big data by individuals and organisations (Bassett, 2015;Kennedy et al, 2014. For instance, in their study of public sector organisations' use of digital data analysis tools, Kennedy et al (2014 found a skills and expertise divide in data generation and collection, use of datacollection tools and data analysis.…”
Section: Digital Methods Data and Expertisementioning
confidence: 99%
See 2 more Smart Citations
“…Developments in digital methods have provided researchers with approaches and tools with which to study social media sociologically (Baym, 2013;Bennett & Segerberg, 2012;Burgess & Bruns, 2012;Gerrard, 2018;Halfpenny & Procter, 2015;Kennedy, Moss, Birchall, & Moshonas, 2015;Lupton, 2014;Marres, 2017;Rieder, 2013Rieder, , 2015aRieder, , 2015bRoberts, Snee, Hine, Morey, & Watson, 2016;Zimmer & Proferes, 2014). These digital methods have in some ways benefitted from the 'platformisation' of the web, in which web applications, including social media, are increasingly integrated with each other and the wider web, facilitating increased flows of data and information (Helmond, 2015).…”
Section: Platformisation Of the Webmentioning
confidence: 99%